INOVASI PEMBELAJARAN RUKUN ISLAM MENGGUNAKAN MEDIA INTERAKTIF QUIZZ DI TADIKA AL-FIKH ORCHARD BANDAR PARKLANDS, KLANG - Rana Alfiyah; Mavianti Mavianti (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
An integral part of Islamic religious education is learning the Five Pillars of Islam. However, the ideas behind the Five Pillars of Islam are difficult for many students to understand and memorize. This is due to the lack of interactivity and reliance on traditional teaching methods. Students lose interest in learning and end up forgetting what they have learned. As a result, Islamic Religious Education must adopt more modern teaching approaches to make the lessons more interesting and useful for students. Interactive quiz-based media, such as the Quizizz app, can be used as one method. Using the Quizizz app in particular, this study aims to investigate new ways of teaching the Five Pillars of Islam through interactive quiz media. By observing one Malaysian kindergarten, this descriptive qualitative research aims to. The study analyzed the impact of using Quizizz on students' understanding and engagement in learning the Five Pillars of Islam. The subjects of this study were children studying at Tadika Alfikh Orchard, Bandar Parklands, Klang. The research findings show that the use of Quizizz and other forms of interactive media can arouse students' interest in learning the pillars of Islam and improve their understanding of the subject matter.